Formulation and Evaluation of Duloxetine Hydrochloride (Enteric Coated) Tablets - Das, Sudipta; Halder, Pallab (Asian Journal of Chemistry, 2010)
Duloxetine hydrochloride was tried to be formulated as enteric coated tablet using hypromellose phthalate (HP-55) as enteric coated materials in various proportions. Thus three formulations were prepared and all of them had same amount of ingredients but only difference in percentage of coating applied. In vitro evaluation were carried out by using U.P.S. dissolution testing apparatus. Successful formulation was found good release profile in 45 min. One commercial tablet was compared with this formulated tablets.